2019
DOI: 10.1016/j.wroa.2019.100036
|View full text |Cite
|
Sign up to set email alerts
|

Current time-temperature relationships for thermal inactivation of Ascaris eggs at mesophilic temperatures are too conservative and may hamper development of simple, but effective sanitation

Abstract: Ascaris eggs are commonly used as indicators for pathogen inactivation during the treatment of fecal sludge and wastewater due to their highly resistant lipid membrane and ability to survive in the environment for long periods of time. Current guidelines suggest that thermal treatment alone cannot inactivate Ascaris eggs at temperatures below 45 °C, although some evidence in the literature suggests this to be incorrect. Here, we performed a controlled experiment to test the effect of mesophilic temperatures on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…They observed inactivation in AD at temperatures between 37 and 45 • C, while at lower temperatures Ascaris stayed active. The time required for a 3-log reduction in Ascaris' viability decreased from 57.5 to 2.12 days as the temperature increased [23]. Ligocka and Paluszak [30] who compared composting and fermentation under mesophilic conditions have also confirmed that the fastest inactivation during AD is taking place at 55 • C. A decrease in the percentage of invasive eggs amounted to almost 8% per hour [30], which is similar to a decrease obtained in present research (6.7-7.1%/h).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…They observed inactivation in AD at temperatures between 37 and 45 • C, while at lower temperatures Ascaris stayed active. The time required for a 3-log reduction in Ascaris' viability decreased from 57.5 to 2.12 days as the temperature increased [23]. Ligocka and Paluszak [30] who compared composting and fermentation under mesophilic conditions have also confirmed that the fastest inactivation during AD is taking place at 55 • C. A decrease in the percentage of invasive eggs amounted to almost 8% per hour [30], which is similar to a decrease obtained in present research (6.7-7.1%/h).…”
Section: Resultsmentioning
confidence: 95%
“…Papajova et al [29] stated that exposing A. suum eggs to the thermophilic conditions is the best way of elimination, due to inactivation of the enzymatic system of the egg. Harrof et al [23] investigated the time-temperature relationship for the inactivation of Ascaris eggs under mesophilic temperatures in aerobic and anaerobic treatment. They observed inactivation in AD at temperatures between 37 and 45 • C, while at lower temperatures Ascaris stayed active.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if a thermophilic temperature is not achieved, a small change in temperature in the mesophilic range facilitates the inactivation of Ascaris eggs. 95 Pathogen inactivation in a composting chamber primarily relies on the heat generated by aerobic biological reactions. Thus, maintaining optimum conditions for biological reactions is important for sanitization.…”
Section: Sanitation Technologies For Agri-resource Recoverymentioning
confidence: 99%
“…Ascaris eggs are not inactivated at temperatures below 36 °C without uncharged ammonium. 95,121 At a thermophilic temperature, the estimated storage time was significantly shortened to <1 d for bacteria and Ascaris eggs and 30 d for murine norovirus 1 (Fig. 4 and Table S5 †).…”
Section: 23mentioning
confidence: 99%